Ecstasy, catastrophe : Heidegger's being and time and the black notebooks - Krell, David Farrell (SUNY series in contemporary continental philosophy., 2015)
In Ecstasy, Catastrophe, David Farrell Krell provides insight into two areas of Heidegger's thought: his analysis of ecstatic temporality in Being and Time (1927) and his "political" remarks in the recently published Black Notebooks (1931-1941). The first part of Krell's book focuses on Heidegger's interpretation of time, which Krell takes to be one of Heidegger's greatest philosophical achievements. In addition to providing detailed commentary on ecstatic temporality, Krell considers Derrida's analysis of ekstasis in his first seminar on Heidegger, taught in Paris in 1964-1965. Krell also relates ecstatic temporality to the work of other philosophers, including Aristotle, Augustine, Kant, Schelling, Hölderlin, and Merleau-Ponty; he then analyzes Dasein as infant and child, relating ecstatic temporality to the "mirror stage" theory as Jacques Lacan. The second part of the book turns to Heidegger's Black Notebooks, which have received a great deal of critical attention in the press and in philosophical circles. Notorious for their pejorative references to Jews and Jewish culture, the Notebooks exhibit a level of polemic throughout that Krell takes to be catastrophic in and for Heidegger's thought. Heidegger's legacy therefore seems to be split between the best and worst of thinking - somewhere between ecstasy and catastrophe. -- from dust jacket.